996Factors predicting retention among people accessing outpatient methadone maintenance therapy in Tshwane, South Africa. (2nd September 2021) - Gloeck, Natasha Rachel; Harris, Bernice; Webb, Elizabeth; Scheibe, Andrew
Abstract: Background: In South Africa, increasing illicit opioid use and associated health challenges can be managed with opioid substitution therapy (OST), like methadone, provided it is prescribed at the recommended dose and duration. The Community Oriented Substance Use Programme (COSUP) provides free methadone to patients with Opiod Use Disorder across Tshwane, South Africa on need-based criteria. Methods: A retrospective cohort using secondary data of patients treated with methadone at eight COSUP sites. The factors associated with the retention of 575 participants for the period December 2016 to September 2018 were analysed. Results: Participants on lower methadone doses had decreased odds of being retained (0 to 20mg: adjusted odds ratio (aOR) 0.25, p-value (p)=0.002, 95% Confidence Interval (CI) 0.10 - 0.61; 20 to 40mg: aOR 0.20, p < 0.001, 95% CI 0.08 - 0.49). Participants receiving free methadone had 3.75 the odds to be retained (p < 0.001, 95% CI 2.47 - 5.70). Inner-city participants had 5.19 the odds to be retained (p < 0.001, 95% CI 2.99 - 9.03). White participants had 3.39 the odds of being retained (p = 0.001, 95% CI 1.64 - 7.00). Injecting heroin users had 0.63 the odds of being retained (p = 0.032; 95% CI 0.41 - 0.96). Conclusions: Methadone doses above 50mg, access to free methadone, accessing care within the inner-city and the white population group were positively associated with retention. Injecting drug use was negatively associated. Key messages: Provision of free methadone at adequate doses can aid in retaining patients within an outpatient OST programme.